2003
DOI: 10.1063/1.1556131
|View full text |Cite
|
Sign up to set email alerts
|

Universal scaling of magnetoconductance in magnetic nanocontacts (invited)

Abstract: We present results of half-metallic ferromagnets formed by atomic nanocontact of CrO 2 -CrO 2 and CrO 2 -Ni that show as much as 400% magnetoconductance. Analysis of the magnetoconductance versus conductance data for all materials known to exhibit so-called ballistic magnetoresistance strongly suggests that the magnetoconductance of nanocontacts follows universal scaling. If the maximum magnetoconductance is normalized to unity and the conductance is scaled to the resistivity of the material, then all data poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…On the one hand, it has been argued that magnetic field-induced mechanical effects can produce a large GMR. In fact, either magnetostriction, dipole-dipole interactions between the apexes 14 and magnetically induced stress relief 15 may have the effect of compressing the nanocontact once a magnetic field is applied. This enlarges the cross section of the MPC and consequently the resistance of the junction decreases.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, it has been argued that magnetic field-induced mechanical effects can produce a large GMR. In fact, either magnetostriction, dipole-dipole interactions between the apexes 14 and magnetically induced stress relief 15 may have the effect of compressing the nanocontact once a magnetic field is applied. This enlarges the cross section of the MPC and consequently the resistance of the junction decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an MR ratio of 100,000% was observed in a point-contact (PC) between two bulk Ni wires, which were connected by electrodeposition [2]. A large MR ratio explained as ballistic MR (BMR) can be experimentally observed with electroplated or bulk PCs [3,4]. These large BMR phenomena are attractive for MR sensor applications.…”
Section: Introductionmentioning
confidence: 95%
“…Fabricating a nano-scale size PC in a magnetic metal film is not easy, even with electronbeam lithography [6]. In addition, MR measurements of metallic PCs in air are difficult because of their rapid oxidation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Control over tip shape is also important in making ferromagnetic nanocontacts to obtain giant magnetoresistance [2][3][4]. Recent studies have shown that a magnetoresistance of several thousand percent can be achieved by means of a metal probe with a tip of radius ~ 100 nm on which nickel or other metal has been deposited electrochemically [5,6].…”
Section: Introductionmentioning
confidence: 99%